The Hubs of Transformation Dictated by the Innovation Wave: Boston as a Case Study: Exploring How Design is Emerging as an Essential Feature in the Process of Laboratorization of Cities - Luana Parisi; Sohrab Donyavi (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Cities have become nodes of global networks, standing at the intersection points of the flows of capital, goods, workers, businesses, and travelers, making them spots where innovation, progress and economic development occur. Design emerges as an essential feature in this process, which this manuscript defines as the ‘laboratorization of cities’, a cutting-edge urban development paradigm that emphasizes cities as dynamic laboratories for innovation and experimentation. This study explored the spatial hubs of transformation within the knowledge economy, providing an overview of the current models of innovation spaces before focusing on the innovation district of one of the cities that are riding the innovation wave, namely Boston, USA. Information was gathered from observations, exploratory interviews with key stakeholders, and on-desk data. The study has significant implications, spanning from informing global urban development strategies to impacting regional economic planning and national policies. It provides valuable insights into how design, innovation, and urban development are interconnected, potentially reshaping how cities and regions approach their growth in the current knowledge-driven era. Useful lessons can be drawn from the case study analysis, allowing to define valuable tools for policymakers, a forward-looking perspective on the future of the laboratorization of cities and the evolving role of design, providing a roadmap for cities aiming to position themselves as global innovation hubs.